Applying of Fatwa in the Case of Islamic Banking in Court: A Study of the Development of Islamic Banking in Indonesia - Jalil, Andi Wahyudin; Yani, Achmad (International Journal of Law and Public Policy (IJLAPP), 2021)
This research generally aims to examine the things that need to be considered in advancing Islamic banking. The research method used to achieve the research objectives is a qualitative research design with a research strategy through case analysis, data collection methods in interviews, and data analysis methods in analytical content. This study recommends how the Islamic banking in expanding the Islamic banking market. Based on the research, in general, there are 3 main agendas that need attention in advancing Islamic banking, namely national policy support, expansion of Islamic economic and financial institutions, and the last is education and inculcation of Islamic economic values and concepts.